2024
DOI: 10.1007/s41999-024-00953-8
|View full text |Cite
|
Sign up to set email alerts
|

Rising to the challenge of defining and operationalising multimorbidity in a UK hospital setting: the ADMISSION research collaborative

Rachel Cooper,
Jonathan G. Bunn,
Sarah J. Richardson
et al.

Abstract: Purpose Greater transparency and consistency when defining multimorbidity in different settings is needed. We aimed to: (1) adapt published principles that can guide the selection of long-term conditions for inclusion in research studies of multimorbidity in hospitals; (2) apply these principles and identify a list of long-term conditions; (3) operationalise this list by mapping it to International Classification of Diseases 10th revision (ICD-10) codes. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Work on specifying the conditions which should contribute to definitions of MLTC has progressed in recent years, with work by Ho et al. and the ADMISSION collaborative aiming to standardise definitions used across studies [ 5 , 169 ]. While a standardised methodology for delirium ascertainment remains challenging, optimising the assessment of delirium in research studies has been identified as an essential target to advance delirium practice and knowledge [ 170 ].…”
Section: Discussionmentioning
confidence: 99%
“…Work on specifying the conditions which should contribute to definitions of MLTC has progressed in recent years, with work by Ho et al. and the ADMISSION collaborative aiming to standardise definitions used across studies [ 5 , 169 ]. While a standardised methodology for delirium ascertainment remains challenging, optimising the assessment of delirium in research studies has been identified as an essential target to advance delirium practice and knowledge [ 170 ].…”
Section: Discussionmentioning
confidence: 99%